Characteristics of self-management among patients with complex health needs: a thematic analysis review - Catherine Hudon; Maud-Christine Chouinard; Annie-Pier Gobeil-Lavoie; Alya Danish (BMJ Open)
Objective There is a gap of knowledge among healthcare providers on characteristics of self-management among patients with chronic diseases and complex healthcare needs. Consequently, the objective of this paper was to identify characteristics of self-management among patients with chronic diseases and complex healthcare needs.Design Thematic analysis review of the literature.Methods We developed search strategies for the MEDLINE and CINAHL databases, covering the January 2000–October 2018 period. All articles in English or French addressing self-management among an adult clientele (18 years and older) with complex healthcare needs (multimorbidity, vulnerability, complexity and frequent use of health services) were included. Studies that addressed self-management of a single disease or that did not have any notion of complexity or vulnerability were excluded. A mixed thematic analysis, deductive and inductive, was performed by three evaluators as described by Mileset al.Results Twenty-one articles were included. Patients with complex healthcare needs present specific features related to self-management that can be exacerbated by deprived socioeconomic conditions. These patients must often prioritise care based on one dominant condition. They are at risk for depression, psychological distress and low self-efficacy, as well as for receiving contradictory information from healthcare providers. However, the knowledge and experiences acquired in the past in relation to their condition may help them improve their self-management skills.Conclusions This review identifies challenges to self-management for patients with complex healthcare needs, which are exacerbated in contexts of socioeconomic insecurity and proposes strategies to help healthcare providers better adapt their self-management support interventions to meet the specific needs of this vulnerable clientele.